A origem das crises financeiras internacionais: fracos fundamentos ou puro contágio? uma análise empírica - Milton de Assis (Economia Aplicada, 2002)
Some analysts defend that there is a pattern of contagion for the international financial crises defined by weak macroeconomic fundamentals while for others the pattern of contagion is random and results from investors irrational behavior and/or destabilizing speculation. The empirical analysis conductedby Sachs (1996) forthe Mexican crises and Stiglitz (1998), using the Sachs model, for the Asian crises are the basic references for this controversy. Additional empirical works by Kaminsky and Reinhart (1998), Glick and Rose (1998) and Berg and Patillo (1999) among others, reached conflicting results. This article is an econometric analysis ofthe contagion occurred during the Mexican, Asian and Brazilian crises, using a different version of the Sachs model incorporating composite variables and updated statistics for 22 developing countries. The pooling time series cross section data analysis used in the study improved the statistical inference and increased the degrees offreedom in the parameters estimates and, when compared with the econometric analysis of each crises, helped check the hypothesis of a single pattern for all financial crises.The analysis suggests that the spreading ofcrises depends heavily on the irrational behavior oftlie markets, but does not rejectthe hypothesis that weak fundamentals may play some role starting the contagion process. The conclusion is that a country to protect itselffrom contagion crises should complement good fundamentals with a contingency credit line from the IMF and constrain the short-tenn capital volatility.